Prediction of job engagement of teachers based on psychological capital and psychological hardiness - khaleghkhah, Ali; Zahed babelan, Adel; karimianpour, Ghaffar (Revista de la Universidad del Zulia, 2019)
The present research was carried out with the objective of predicting job engagement based on psychological capital and hardiness. This was a descriptive and correlational research. Research population consisted of all primary school teachers of Javanroud city and 195 samples were selected based on Cochran’s formula and with the use of stratified random sampling. Findings showed that there is a significant positive relation between psychological capital and hardiness and job engagement of employees. Also the results of multiple regression analysis revealed that about 55 percent of total job engagement of employees is predictable based on psychological capital and hardiness in which psychological variable had greater share in prediction.